Optimized saturation pulse train for human first-pass myocardial perfusion imaging at 7T - Tao, Y; Hess, A; Keith, G; Rodgers, C; Liu, A; Francis, J; Neubauer, S; Robson, M (Wiley, 2015)
To investigate whether saturation using existing methods developed for 3T imaging is feasible for clinical perfusion imaging at 7T, and to propose a new design of saturation pulse train for first-pass myocardial perfusion imaging at 7T.The new design of saturation pulse train consists of four hyperbolic-secant (HS8) radiofrequency pulses, whose peak amplitudes are optimized for a target range of static and transmit field variations and radiofrequency power deposition restrictions measured in the myocardium at 7T. The proposed method and existing methods were compared in simulation, phantom, and in vivo experiments.In healthy volunteer experiments without contrast agent, average saturation efficiency with the proposed method was 97.8%. This is superior to results from the three previously published methods at 86/95/90.8%. The first series of human first-pass myocardial perfusion images at 7T have been successfully acquired with the proposed method.Existing saturation methods developed for 3T imaging are not optimal for perfusion imaging at 7T. The proposed new design of saturation pulse train can saturate effectively, and with this method first-pass myocardial perfusion imaging is feasible in humans at 7T.